A Study to Assess Depression, Anxiety, Loneliness and Internet Addiction among College Students Using Internet in Selected College, Chennai (Medico Legal Update, 2020)
A study to assess depression, anxiety, loneliness and internet addiction among college students using internetin selected colleges, Chennai. Majority of the participants were males, were 20 years old, residing in urbancommunity, used their mobile for internet services, used internet first time in the school, spent more than4 hrs/day on internet, spend Rs. 300/- per month and use the internet for study, online purchase,whats app& face book, you tube. Majority of the participants had mild level of internet addiction. Equal number ofparticipants had mild, borderline and moderate level of depression (16.3% each). Minority of them reportedextreme depression. Majority of the participants had mild anxiety and minority had severe anxiety. Majorityof the participants had mild level of loneliness and minority had moderate level of loneliness. Source ofinternet, browsing duration/day and amount spent for the internet are significantly associated with internetaddiction. Browsing duration/day is significantly associated with depression.